Periodic performance evaluation of the public employee: a tool to concretize the principle of efficiency or instrument of control and domination of the public employee? (Research, Society and Development, 2022)
Constitutional Amendment 19/1998 expressly inserted in the Federal Constitution both the Principle of Efficiency and the Periodic Performance Evaluation, in addition to establishing that the Union, the States and the Federal District should maintain government schools for the training and improvement of public employees, among other measures. The objective of this article is to analyze the Periodic Performance Evaluation of the Public Employee, to verify if it can be considered a tool capable of concretizing the Principle of Efficiency in the Public Administration or if it can be used as an instrument of control and domination of the public employee. The methodology used will be bibliographic and qualitative research, through an exploratory study of literature review in books, magazines, legislation, scientific texts, searching for materials that analyze the theme proposing an analytical and critical reflection. As for the results, it was found that despite the Periodic Performance Evaluation being criticized by some authors, for making the stability of the public employee flexible, it can be considered an important tool for achieving Efficiency, as long as it is carried out properly, with objective criteria defined in law, obeying the Principle of Legality, taking into account the organizational culture, with a method capable of carrying it out, minimizing subjectivism and biases and using the schools of government for the improvement of the employees. On the other hand, if it is full of subjectivities, it can serve as an instrument of persecution, control and domination of public employees by their superiors.